GE_GERICHTE P/12795/2019 vom 11. Januar 2022 - GE Cour de justice (2022)
IN DUBIO PRO REO;TENTATIVE(DROIT PÉNAL);MEURTRE;DISPOSITIONS PÉNALES DE LA LCR;LÉGITIME DÉFENSE;TORT MORAL | CP.111; CP.22; LCR.91.al2.leta; LCR.90.al1; CP.15; CP.16; CP.13; CP.47; CO.47; CO.49